ADVANTAGES AND DISADVANTAGES OF ARTIFICIAL INTELLIGENCE IN MODERN TIMES - Odinaxon Erkinova Kozimjon qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: This article provides an in-depth analysis of the role, potential, and existing limitations of artificial intelligence technologies in modern society. The author examines the applications of artificial intelligence in fields such as the economy, education, healthcare, industry, and others. Alongside highlighting its positive impact on human activity, the article also addresses emerging issues, including ethical, legal, and social risks. It offers a systematic analysis grounded in both theoretical foundations and real-life practical examples for the effective use of artificial intelligence. Furthermore, the necessity of establishing a balanced relationship between technological advancement and human progress is substantiated.